Comprehensive analysis of splicing factor SRs-related gene characteristics: predicting osteosarcoma prognosis and immune regulation status - Long, Changhai; Ma, Biao (Frontiers in Oncology, 2024)
ObjectiveTo investigate the impact of SRs-related genes on the overall survival and prognosis of osteosarcoma patients through bulk and single-cell RNA-seq transcriptome analysis.MethodsIn this study, we constructed a prognosis model based on serine/arginine-rich splicing factors (SRs) and predicted the survival of osteosarcoma patients. By analyzing single-cell RNA sequencing data and applying AUCell enrichment analysis, we revealed oncogenic pathways of SRs in osteosarcoma immune cells. Additionally, we described the regulatory role of SRSF7 in pan-cancer.ResultsLasso regression analysis identified 6 key SRs-related genes, and a prognosis prediction model was established. The upregulation of these pathways revealed that SRs promote tumor cell proliferation and survival by regulating related signaling pathways and help tumor cells evade host immune surveillance. Additionally, by grouping single-cell data using AUCell, we found significant differences in T cell expression between high and low-risk groups. The analysis results indicated that the regulatory activity of SRs is closely related to T cell function, particularly in regulating immune responses and promoting immune evasion. Furthermore, SRSF7 regulates cell proliferation and apoptosis.ConclusionSRs-related genes play a critical regulatory role in osteosarcoma. T cells are key in regulating immune responses and promoting immune evasion through SRs genes. SRSF7 is a significant gene influencing the occurrence and development of osteosarcoma.